Replaying Empire: Racialized Violence, Insecure Frontiers, and Displaced Terror in Contemporary Video Games - Leonard, David J.; King, C. Richard (Ethnicity and Race in a Changing World, 2009)
In the wake of 9/11, US popular culture has played an important role in the manufacture of consent and the mediation of contradictions. In particular, video games have aff orded the production of interactive, narrative spaces for the reassertion of race, nation, and gender. Through a close reading of two video games, Gun and Ghost Recon Advanced Warfighter 2, we unpack the insecurities of empire and how racialized violence, colonial categories, and territorial claims work to resecure Whiteness, masculinity, and Americanness. Special attention is given to the militarization of video games and rhetorical struggles over the meaning of race and culture amid the ‘War on Terror’.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé